(untitled) (Szociológiai Szemle, 2024)
In this paper we analyze whether and how unemployment patterns changed during the transition from socialism to capitalism in Hungary and Poland. Specifically, we test two competing theories that make predictions about women’s employment outcomes as a result of market reforms. First, Fodor’s theory of "revalued resources" predicts that women will have a significant advantage over men in the labor market as a result of attaining high levels of education and gaining substantial work experience in the service-sector under the socialist regime. Alternatively, the "re-traditionalization" theory predicts that women’s employment will gradually deteriorate as a result of traditional gender ideologies that have re-emerged throughout the transitional period. In order to adjudicate between these competing theories, our analysis draws upon two major cross-national surveys conducted in Central and Eastern Europe in 1993 and 2000. By comparing labor market figures in Hungary and Poland in 1988, 1993, and 2001, our analysis maps the trajectory of men and women’s unemployment from the period immediately preceding market reforms to the current phase of transition. Overall, we find modest evidence for both theories depending on the country of interest. Furthermore, while women, as compared to men, have sustained a relatively strong position in the labor market after over a decade of reforms in Hungary, the employment situation for women in Poland is becoming increasingly bleak.